Evaluasi Biaya Pengembangan Perangkat Lunak Dengan Menggunakan Metode Extended Use Case Point Dan Use Case Size Point - Farinda Ristanti; Admaja Dwi Herlambang; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In calculating the cost estimation of project, software house doesn't have any standards, and suggested in every construction project refers to the execution of a structured on the Work Breakdown Structure (WBS). This research lay's out used WBS and scheduling using Gantt Chart, as well as the calculation of the estimated costs of using metode Extended Use Case Point and Use Case Size Point. Data collection technique was done by interviewed and deployment assessment sheet for developer and software observation, then the result will be used as material to make use case diagram and use case scenario for calculation of Extended Use Case Point and Use Case Size Point. Extended Use Case Point estimated effort 25 people during 118,1 hours and the total estimated cost was Rp 70.252.030,00. While Use Case Size Point produce the effort 25 people during 91,2 hours and the total estimated cost is Rp 56.747.500,00. From the comparison of the two methods, the calculation of cost estimation using the Use Case Size Point method is recommended, because it has a smaller accuracy than the method of Extended Use Case Point, which is 3,1%.